Influence of Nano-Methionine supplementation in drinking water on growth performance, lipid metabolism, and related gene expression in broiler chicken - Set A. El-Shobokshy; Magda I. Abo-Samaha; Eman M. Abd El-Maksoud; Shymaa A. Khatab; Asmaa F. Khafaga; Gemechu Wirtu (Journal of Advanced Veterinary and Animal Research, 2022)
Objectives: The study aimed to determine how Nano-Methionine (Nano-Meth) affected growth, lipid metabolism, and relative gene expression for acetyl-CoA carboxylase (ACC), fatty acid syn¬thase (FAS), growth hormone receptor (GHR), insulin-like growth factor receptor-1 (IGFR-1), myo¬statin (MSTN), and cholecystokinin (CCK) genes in broiler chickens. Materials and Methods: A total of 100 1-day-old broilers were randomly assigned into 2 groups: 1) the control group received drinking water without any supplements, and 2) the Nano-Meth group received 10 ml/l of 5% Nano-Meth starting from 1 day old until 35 days old (the end of the experiment). Results: Nano-Meth improved final body weight, weight gains, feed intake, and feed conver¬sion ratio. Compared to the control group, Nano-Meth significantly lowered the serum levels of triglyceride, cholesterol, very low-density lipoprotein, and low-density lipoprotein in chickens. Nano-Meth significantly increased the serum levels of total protein, albumin, high-density lipo-protein, and glucose more than the control group. Nano-Meth lowered the mRNA gene expression of ACC, FAS, MSTN, and CCK but increased that of GHR and IGFR-1. Conclusions: We concluded that supplementation with Nano-Meth enhances growth performance and decreases lipid accumulation in broiler chickens. [J Adv Vet Anim Res 2022; 9(4.000): 743-753]